(untitled) (Eurasian Medical Research Periodical, 2024)
The study assessed the gender as a correlate of nutritional health status of early childhood and preschool children aged 1-5 years in Akwa Ibom State. In carrying out the study, a cross-sectional survey design was adopted as the study. The study was conducted in Akwa Ibom State, Nigeria. The targeted population for the study comprised school children registered in government approved nursery and primary schools aged 1-2 years and 3-5 years in Akwa Ibom State. Multi stage sampling procedure was used to draw a total of 1440 pupils from urban and rural nursery/primary schools in Akwa Ibom State Senatorial districts. Data for the study were collected using standardized instruments and proforma for anthropometric assessment. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. No test of reliability was done since the instruments were standardized. The researcher subjected the data generated for this study to appropriate statistical techniques such as descriptive statistics meant to answer the research questions and simple regression analysis meant to test the hypothesis. The test for significance was done at 0.05 alpha levels. The study concluded that it is important that children not only acquire knowledge about adequate nutrition but also develop good eating habits that would enhance their growth and development. It includes proper intake of food, liberation of energy, elimination of wastes and the biochemical syntheses that are essential for maintenance of normal growth and development. One of the recommendations made was that since the goal of every health practitioner is to maintain a high level of nutritional health status for the population, the hospitality industry should always go for regular checkup using anthropometric indicators such as weight for height (W/H), weight for age (W/A) and height for age (H/A) to characterize the nutritional status of populations.